Possible Anti-Asthmatic Effect of Iraqi Ammi Majus Seeds Extract Against Asthma Induced by Ovalbumin in Mice - Zainab T. Younis; H. Mutlag, Shihab (Iraqi Journal of Pharmaceutical Sciences, 2023)
Asthma is a chronic respiratory disorder of airways characterized by inflammation, hyperresponsiveness, inflammatory cell infiltration, mucous secretion, and remodelling. Ammi majus is medicinal plant belong to family of Apiaceous which has anti-inflammatory and antioxidant activities. This study designed to investigate of anti-asthmatic activity of alcoholic extract of Ammi majus in improvement of asthma. Forty-eight healthy female mice divided to six groups Group I: the negative control group (distal water only), Group II: Positive control group (ovalbumin group), Group III: Ammi majus (64 mg/kg/day) with sensitization, Group IV:Ammi majus (128 mg/kg/day) with sensitization, Group V: Ammi majus (64 mg/kg/day) without sensitization, Group VI: Ammi majus (128mg/kg/day) without sensitization. Mice were sacrificed by diethyl ether and blood samples were collected to prepare of serum samples that used in ELISA kits for measuring of parameter IL-4, IL-5, IL-33, & IgE. Levels of all parameters (IL-4, IL-5, IL-33, & IgE) for mice of treated groups with alcoholic extract of Ammi majus were highly significant reduced (p<0.05) in compared to ovalbumin group.in conclusion, our results demonstrated that alcoholic extract of Ammi majus has a potent anti asthmatic activity that improved ovalbumin-induced asthma.